Sexual dimorphism of the planum temporale in schizophrenia: A MRI study. (October 2017) - Delvecchio, Giuseppe; Pigoni, Alessandro; Perlini, Cinzia; Barillari, Marco; Ruggeri, Mirella; Altamura, Alfredo Carlo; Bellani, Marcella; Brambilla, Paolo
Objective: Anatomical alterations in the superior temporal gyrus have been consistently reported in patients with schizophrenia, and they have mostly been linked to positive symptoms, including hallucinations and thought disorders. The superior temporal gyrus is considered one of the most asymmetric and lateralized structure of the human brain, and the process of lateralization seems to vary according to gender in the normal population. However, although it has been consistently suggested that patients with schizophrenia did not show normal brain lateralization in several regions, only few studies investigated it in the superior temporal gyrus and its sub-regions considering the effects of gender. In this context, the aim of this study was to evaluate sexual dimorphism in superior temporal gyrus volumes in a sample of patients with schizophrenia compared to age- and gender-matched healthy controls. Methods: A total of 72 right/left-handed males (40 schizophrenia patients and 32 healthy controls) and 45 right/left-handed females (18 schizophrenia patients and 27 healthy controls) underwent clinical evaluation and a 1.5T magnetic resonance imaging scan. Gray and white matter volumes of regions of interest within the superior temporal gyrus were manually detected, including the Heschl's gyrus and the planum temporale. Results: Female patients with schizophrenia presented a reduction in left planum temporale gray matter volumes ( F = 4.58, p = 0.03) and a lack of the normal planum temporale asymmetry index ( t = 0.27; p = 0.79) compared to female controls ( t = 5.47; p = 0.001). No differences were found between males for any volumes or laterality indices. Finally, in female patients with schizophrenia, Heschl's gyrus gray and white matter volumes negatively correlated with positive symptoms ( r = −0.56, p = 0.01). Conclusion: Our results showed that sexual dimorphism plays a key role on planum temporale in schizophrenia, underlining the importance of gender as a modulator of brain morphology and lateralization of schizophrenia.